The role of indoor air pollution and other factors in the incidence of pneumonia in under-five children - Sunyataningkamto Sunyataningkamto; Iskandar Z; Alan R T; Budiman I; Ahmad Surjono; Tunjung Wibowo; Endang Dewi Lestari; Dwi Wastoro (Indonesian Pediatric Society, 2004)
Background The World Health Organization has asked for a spe-cial attention to the relation between pneumonia and indoor airpollution, i.e., household biomass fuel smoke, cigarette smoke,and mosquito coil smoke, especially in developing countries.Objective To analyze the role of indoor air pollution and otherfactors as risk factors for pneumonia in under-five-year children.Methods This case-control study was carried out from August un-til December 2000 at Public Health Centers in Banjarnegara,Kebumen, Jepara, and Pekalongan districts. All children qualify-ing pneumonia classification as recommended by WHO in IMCI(Integrated Management of Childhood Illness) were defined ascases and without pneumonia as controls. Severe pneumonia andno pneumonia (as classified in IMCI) were excluded. Statisticalanalysis was done using bivariate and logistic regression.Results There were three hundreds and five children with pneu-monia and 289 children without pneumonia. By bivariate analysis,biomass fuel smoke (OR=3.25; 95%CI 1.50;7.07) and cigarettesmoke exposure from other family members (OR=1.63; 95%CI1.11;2.38) were risk factors for pneumonia, while mosquito coilsmoke (OR=1.13; 95%CI 0.79;1.69) was not. History of wheezing(OR=2.60; 95%CI 2.7;8.55), malnutrition (OR=2.60; 95%CI1.33;5.07), and male sex (OR=1.47; 95%CI 1.06;2.04) were otherrisk factors.Conclusions Household biomass fuel smoke and cigarette smokewere risk factors for pneumonia. Other variables as risk factorswere history of wheezing, male sex, and malnutrition